Cytological and Histopathological Correlation of Salivary Gland Tumours - Muthumani, L; Muthuraman, M; Mutharasi, C Aruna (Annals of Pathology and Laboratory Medicine, 2022)
Background: Tumours of the salivary gland comprise 3-6% of all tumours of head and neck region. Fine Needle Aspiration Cytology (FNAC) is a widely recognized practical and non-expensive technique to differentiate between the benign and malignant lesions. The objectives of the study are, 1. To study the histopathology of benign and malignant tumours of salivary glands. 2.To correlate cytological and histopathological diagnosis of salivary gland tumours. Method: FNAC was done under strict aseptic precautions with 18–22-gauge needles with 10cc syringe after getting informed and written consent. Slides were fixed in alcohol and stained with Haematoxylin and Eosin. The fixed surgical specimens were processed and sections of 5-micron thickness were cut and stained with Haematoxylin and Eosin Result: Out of the 50 cases studied 39(78%) were benign and 11(22%) were malignant. In the present study out of 41 cases reported as benign in cytology, 38 were proved to be benign and three cases turned into malignant in histopathology. The sensitivity, specificity and accuracy of cytological diagnosis to diagnose benign lesions are 92.8%, 100% and 94% respectively. In the present study out of eight cases reported as malignant tumour, all were later proved in histopathology as malignant. The sensitivity, specificity and diagnostic accuracy of cytology to diagnose malignant tumours are 75.4%, 100% and 94% respectively. Conclusion: Thus FNAC is the safe, reliable, quick, convenient and accurate method of diagnosis and should be considered as one of the first line investigations in the evaluation of salivary gland lesions.